Pengaruh Penggunaan Metode Bercerita Story Reading terhadap Perilaku Sosial Anak - Winda Nidya Putri Fitriana; Hartin Kurniawati; Mustika Dewi Muttaqien (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
This research was conducted to determine the relationship between the use of the story reading method of children's social behavior. After being given treatment in the form of the story reading storytelling method in the experimental group, it showed an increase in social behavior of children aged 4-5. In the experimental group the results of the pre-test observation (Y1) were 2407 and the results of the final observation (post test) showed higher data 2639. Based on the results of the experimental group pre-test and post-test data, there is a difference in the score between the post-test and pre-test with a difference of 200. So it can be concluded that there are differences in social behavior of children aged 4-5 years before being given treatment, namely the storytelling method. story reading after being given the story reading storytelling method treatment. After being given the treatment, the results of the final observation showed that the data score increased and showed that the story reading method can improve the social behavior of children aged 4-5 years.